The Linkage of Proactive Personality, Emotional Exhaustion and Creativity - Wijaya, Nikodemus Hans Setiadi; Kusumawati, Heni; Prajogo, Wisnu (International Journal of Psychosocial Rehabilitation, 2020)
When emotional exhaustion (a feeling of burn-out and drained) is highly possible to be experienced by employees, its relationship with proactive personality and employee creativity have been ignored to investigate. Using 186 employees working in education institutions, this study found negative relationships between proactive personality and emotional exhaustion and between emotional exhaustion and creativity. Proactive personality of respondents could moderate the effect of emotional exhaustion on creativity. Both theoretical and practical contributions are described. Limitations and directions for future research are also addressed.